Lonergan in the World Self-Appropriation, Otherness, and Justice - Marsh, James (University of Toronto Press, 2018)
In his philosophical classic Insight, Catholic philosopher and theologian Bernard Lonergan introduced the concept of self-appropriation – the personal search for knowledge of the self, and through that of the world – as the basis for systematic philosophical investigation.In Lonergan in the World, James L. Marsh argues, clearly and passionately, that self-appropriation can serve as the basis for philosophical, ethical, and even political and economic thought. Comparing and applying Lonergan’s principles to major trends in contemporary philosophy, including phenomenology, hermeneutics, postmodernism, analytic philosophy, and Marxism, Marsh uncovers the philosophical and the socio-political implications of Lonergan’s work and its value as the basis for a search for justice and self-understanding.Drawing on Marsh’s more than forty years of studying and teaching Lonergan’s thought, Lonergan in the World is a book that should be read not just by philosophers and theologians, but by anyone interested in the philosophical foundations of a just and authentic life